Comparative study of thermal and magnetic properties of CeTyX4-y ferromagnets - Sereni, J.G.; Trovarelli, O.; Schmerber, G.; Kappler, J.P.; Sereni, Julián (American Physical Society, 1997)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina